Relationship-Driven Policy Engineering for Autonomic Organisations - FEENEY, KEVIN; LEWIS, DAVID; O'SULLIVAN, DECLAN; QUINN, KARL ANDREW; WADE, VINCENT PATRICK (IEEE, 2005)
Autonomic systems are needed to self-manage the increasing complexity of pervasive communications access and the ubiquitous computing services it offers to humans. Policy based governance is the means by which humans will impose their will upon how autonomic systems manage themselves. Ultimately, these systems mediate information and services between people, in a rich tapestry of human associations formed though personal, commercial, and civic relationships. Therefore, if policies are to accurately reflect the wishes of their human authors, the process of authoring or engineering them must closely reflect the intricacies and fluidity of human relationships. We see this as the route to providing intuitive use of policy systems and thus to autonomic systems in empowering their users. We have previously presented a scheme for community-based management that addressed the dynamic organizational aspects of human relations in policy authoring. In this paper we review developments with this approach and describe its integration with a trust management system designed to flexibly regulate access to resources according to the trust relationships between participants. This approach promises to enable autonomic organisations, with structures that automatically adapt to the collective needs of the users.
PUBLISHED
Keywords: Computer Science